Recent developments in differential scanning calorimetry for assessing oxidative deterioration of vegetable oils - Tan, C.P.; Che Man, Y.B. (Elsevier Science, 2002)
Differential scanning calorimetry (DSC) is one of the most frequently used analytical instruments in the field of oils and fats. Today, it is already an established technique for characterizing the physical properties of many materials. The possibility of using DSC to characterize oils and fats has been realized for over 50 years. The wide variety of different applications investigated during this period reflects the diversity and complexity of oils and fats materials, as well as the versatility of the DSC technique. The main purpose of this article is to review the latest developments in the use of DSC to evaluate the oxidative deterioration of vegetable oils.